2016
DOI: 10.17957/ijab/15.0114
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Silver Nano-particles on the Salt Resistance of Tomato (Solanum lycopersicum) during Germination

Abstract: To cite this paper: Almutairi, Z.M., 2016. Influence of silver nano-particles on the salt resistance of tomato (Solanum lycopersicum) during germination. AbstractSilver nanoparticles (AgNPs) have been implicated to enhance seed germination and plant growth, improve photosynthetic quantum efficiency and act as antimicrobial agents to manage plant diseases. The role of nanoparticles in the improvement of plant tolerance to environmental stresses such as drought and salinity remains unclear. In this study, we ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(45 citation statements)
references
References 50 publications
0
45
0
Order By: Relevance
“…This may be explained by the enhancement of the different biochemical reactions and water absorption as indicated by a marked increase in GP, shoot length and other growth characteristics. Similarly, Bhati-Kushwaha et al (2013) and Almutairi (2015) reported that the AgNPs appeared to mitigate the deleterious effect of chilling and salinity in wheat and Solanum lycopersicum L., respectively. Likewise, nano-silicon as well as nano zinc oxide were capable of improving salt resistance in some plants (Sedghi et al, 2013 andKalteh et al, 2014).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…This may be explained by the enhancement of the different biochemical reactions and water absorption as indicated by a marked increase in GP, shoot length and other growth characteristics. Similarly, Bhati-Kushwaha et al (2013) and Almutairi (2015) reported that the AgNPs appeared to mitigate the deleterious effect of chilling and salinity in wheat and Solanum lycopersicum L., respectively. Likewise, nano-silicon as well as nano zinc oxide were capable of improving salt resistance in some plants (Sedghi et al, 2013 andKalteh et al, 2014).…”
Section: Discussionmentioning
confidence: 91%
“…However, other studies have demonstrated that AgNPs play an important role in enhancing seed germination and plant growth in different plant species such as Brassica juncea (Sharma et al, 2012), Helianthus annuus and Glycine max (Shelar & Chavan, 2015). Furthermore, application of AgNPs has been found quite effective in improving resistance against salinity during germination of Foeniculum vulgare Mill and Solanum lycopersicum L. (Almutairi, 2015). Although the potential of AgNPs in improving salinity resistance has been reported in several plant species (Ekhtiyari & Moraghebi, 2011), however its role in the alleviation of salinity effect and related mechanisms is still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Germination is the first stage of plant phenology, which is affected by root zone salinization due to excessive salts in growing medium (Farooq et al, 2015;Almutairi, 2016). Salinity causes an increase in root zone osmotic pressure, which ultimately results in cell dehydration and accumulation of higher amount of Na + and Cl -ions in soil solution that disturbs the availability of the nutrient especially K + (Hasanuzzaman et al, 2013;Farooq et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, nanotechnology such as using nanoscale fertilizer may offer new techniques to be used for crop management. The efficient use of nano-scale microelements was reported by many authors including titanium (Hasanpour et al 2015;Singh and Lee 2016;Tan et al 2017) silicon (Siddiqui et al 2014;Ashkavand et al 2015;Sabaghnia and Janmohammadi 2015;Qados and Moftah 2015;Liu et al 2015;Wang et al 2015;Mahdavi et al 2016) silver (Seghatoleslami et al 2015;Almutairi 2016) iron (Martínez-Fernández et al 2015;Pourjafar et al 2016) zinc (Seghatoleslami and Forutani 2015;Soliman et al 2015). The previous reports also described the role of nanomaterials in ameliorating biotic stress in plant habitat.…”
Section: Nanobiotechnology For Crop Productivitymentioning
confidence: 94%